Zinc(ii)-mediated stereoselective construction of 1,2-cis 2-azido-2-deoxy glycosidic linkage: assembly of Acinetobacter baumannii K48 capsular pentasaccharide derivative - Zhao, Xiaoya (2024)
The capsular polysaccharide (CPS) is a major virulence factor of the pathogenic Acinetobacter baumannii and a promising target for vaccine development. However, the synthesis of the 1,2-cis-2-amino-2-deoxyglycoside core of CPS remains challenging to date. Here we develop a highly α-selective ZnI2-mediated 1,2-cis 2-azido-2-deoxy chemical glycosylation strategy using 2-azido-2-deoxy glucosyl donors equipped with various 4,6-O-tethered groups. Among them the tetraisopropyldisiloxane (TIPDS)-protected 2-azido-2-deoxy-d-glucosyl donor afforded predominantly α-glycoside (α : β = >20 : 1) in maximum yield. This novel approach applies to a wide acceptor substrate scope, including various aliphatic alcohols, sugar alcohols, and natural products. We demonstrated the versatility and effectiveness of this strategy by the synthesis of A. baumannii K48 capsular pentasaccharide repeating fragments, employing the developed reaction as the key step for constructing the 1,2-cis 2-azido-2-deoxy glycosidic linkage. The reaction mechanism was explored with combined experimental variable-temperature NMR (VT-NMR) studies and mass spectroscopy (MS) analysis, and theoretical density functional theory calculations, which suggested the formation of covalent α-C1GlcN-iodide intermediate in equilibrium with separated oxocarbenium-counter ion pair, followed by an SN1-like α-nucleophilic attack most likely from separated ion pairs by the ZnI2-activated acceptor complex under the influence of the 2-azido gauche effect.